2016
DOI: 10.7439/ijbar.v7i9.3550
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and possible association with Metabolic Syndrome

Abstract: Background: Thyroid dysfunctions are the most common forms of endocrine disorder in our country, Thyroid hormones perform a wide array of metabolic functions including regulation of lipids, carbohydrates, protein and electrolytes and mineral metabolism, Thyroid hormones are major regulatory hormones that controls the rate of metabolic function and alteration in the levels of thyroid hormones may be associated with metabolic syndrome Aim: The study was performed to investigate the association between Altered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…He found that average distilled water production is 1.80 lit / m2 per day and average production is 0.20 lit / m2 per hour. While the maximum-daily distilled water production obtained 3.76 lit / m2 and the production of the maximum distilled water is 0.46 lit / m2 per hour; the authors [4] examined "the Development and performance analysis of a domestic". The tests were conducted from June, July, August, September, October, November, and December 2011.…”
Section: Introductionmentioning
confidence: 99%
“…He found that average distilled water production is 1.80 lit / m2 per day and average production is 0.20 lit / m2 per hour. While the maximum-daily distilled water production obtained 3.76 lit / m2 and the production of the maximum distilled water is 0.46 lit / m2 per hour; the authors [4] examined "the Development and performance analysis of a domestic". The tests were conducted from June, July, August, September, October, November, and December 2011.…”
Section: Introductionmentioning
confidence: 99%